Pathways to autism diagnosis in adulthood - Isabelle Dufour; Yohann Chiu; Sébastien Brodeur; Mireille Courteau; Josiane Courteau; Émilie Dubé; Alain Lesage; Éric Fombonne; Mélanie Couture (Journal of Neurodevelopmental Disorders)
Abstract Background This study explored Trajectories of Diagnoses (TDs) preceding a first diagnosis of autism in adulthood. Methods This retrospective cohort study used health administrative data from Quebec, Canada, and included all adults with a first recorded diagnosis of autism between 2012 and 2017. A TDs was defined as a succession of medical records of psychiatric and/or neurodevelopmental conditions over time. These TDs were retrospectively analyzed from 2002 to 2017, using a state sequence analysis of diagnoses, in order: Autism, Intellectual or developmental disabilities (IDDs), Schizophrenia spectrum disorder (SSD), Bipolar Disorder (BD), Depressive Disorder (DD), Anxiety Disorder (AD), Attention-deficit/hyperactivity disorder (ADHD), and Other psychiatric and/or neurodevelopmental conditions. Results The cohort included 2799 adults with a first recorded diagnosis of autism between 2012 and 2017. Several psychiatric and/or neurodevelopmental conditions were recorded since 2002, including AD (77.5%), DD (58.0%), SSD (49.4%), BD (48.3%), and IDDs (33.2%). Results revealed 5 distinct types of TDs. Types 1 (63.8%), 2 (17.6%) and 3 (6%) represented individuals in younger age groups with similar characteristics but with very different sequences of diagnoses, characterized by mixed diagnoses in type 1, SSD and AD in Type 2, and IDDs, DD, AD, and ADHD in type 3. Types 4 and 5 (9.0% and 3.6%), representing middle-aged/older groups, displayed distinctive TDs associated with high healthcare use, almost entirely associated with SSD (Type 4) and BD (Type 5). Conclusion This study proposes a complementary examination of the multiple pathways to diagnosis experienced by adults, highlighting the need to address differential diagnosis and co-occurring psychiatric and neurodevelopmental conditions.